Indian Christians : issues and perspectives - Wilson, Viju (New Delhi : Manohar, 2025)
Religious traditions from both Indic and non-Indic backgrounds have significantly contributed to shaping India$1 (Bs rich and diverse religious culture. While there have been occasional challenges, most religious communities work to uphold the country$1 (Bs pluralistic values. Although the majority of Indians are religious, their faith does not lead to communal division. That said, religious communities in India face both shared and unique challenges, which they address according to the theological and ethical principles of their respective traditions. This book delves into Indian Christianity, examining the specific challenges it faces in today$1 (Bs socio-political and religious context. Though often regarded as a foreign religion, Christianity has been present in India for over two thousand years.s
Keywords: Christianity-India